2018
DOI: 10.1177/2158244018803137
|View full text |Cite
|
Sign up to set email alerts
|

140 Characters of Intoxication: Exploring the Prevalence of Alcohol-Related Tweets and Predicting Their Virality

Abstract: Past research has suggested an associative relationship between social media use and alcohol consumption, especially among the younger generations. The current study takes a generalizable approach to examining the prevalence of posting about alcohol on a popular social media platform, Twitter, as well as examining the predictors of a tweet’s virality. We content-analyzed more than 47.5 million tweets that were posted in March 2015 to explore the prevalence of alcohol-related references, and how alcohol-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In addition to severe long‐term negative consequences (i.e., cancer; Connor, ), alcohol use is also associated with a range of short‐term negative consequences including alcohol‐induced memory loss (Hingson et al., ; Valenstein‐Mah et al., ). Social networking websites have become increasingly popular and are a common outlet for individuals to discuss alcohol and substance use (Alhabash et al., ; Boyle et al., ). But to date, no studies have examined the discussion of alcohol‐related memory loss (i.e., blackouts) on Twitter, despite the value such exploration may have for our understanding of blackout‐related attitudes and behaviors.…”
Section: Alcohol‐related Blackoutsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to severe long‐term negative consequences (i.e., cancer; Connor, ), alcohol use is also associated with a range of short‐term negative consequences including alcohol‐induced memory loss (Hingson et al., ; Valenstein‐Mah et al., ). Social networking websites have become increasingly popular and are a common outlet for individuals to discuss alcohol and substance use (Alhabash et al., ; Boyle et al., ). But to date, no studies have examined the discussion of alcohol‐related memory loss (i.e., blackouts) on Twitter, despite the value such exploration may have for our understanding of blackout‐related attitudes and behaviors.…”
Section: Alcohol‐related Blackoutsmentioning
confidence: 99%
“…For example, a study of 11,236 university students found that 97% used social networking websites and that 71% of these students reported posting alcohol‐related content (Erevik et al., ). On Twitter specifically, Alhabash and colleagues () found that 2% of the nearly 50 million Tweets published in the United States in March 2015 included alcohol‐related content (Alhabash et al., ). Exposure to and engagement with alcohol‐related social networking content may be linked to alcohol use.…”
Section: Alcohol‐related Blackoutsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, we apply doc2vec to samples of text messaging from individual participants in the BlackBerry Project study, then leverage the resultant vectors as input to a standard logistic regression algorithm to predict whether the individual self-reported alcohol use during the time period over which the texts were collected. We achieve above 76.5% accuracy on this binary classification task without the need for curating domain-specific keyword lists or manually filtering individual samples, as are typical in studies of this nature [14,15,16].…”
Section: Chapter 1 Introductionmentioning
confidence: 99%